2015
DOI: 10.2341/13-239-c
|View full text |Cite
|
Sign up to set email alerts
|

Four-year Randomized Clinical Trial to Evaluate the Clinical Performance of a Glass Ionomer Restorative System

Abstract: The use of both materials for the restoration of posterior teeth exhibited a similar and clinically successful performance after four years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 22 publications
6
67
1
16
Order By: Relevance
“…This is in accordance with other published reports stating that the nanocharged resin layer applied to the surface of the GIC will improve its abrasion resistance significantly. 22 The results of the present study showed that EQUIA performed similarly to resin composite that is in accordance with other studies 23,24 reporting that highviscosity GIC can be used as permanent restoration with satisfactory results over 2 years. Long-term resistance to abrasion of high-viscosity GIC can be achieved as long as early wear characteristics are improved and no premature loss of the protective resin layer occurred due to several factors such as aggressive brushing or bruxism.…”
Section: Discussionsupporting
confidence: 81%
“…This is in accordance with other published reports stating that the nanocharged resin layer applied to the surface of the GIC will improve its abrasion resistance significantly. 22 The results of the present study showed that EQUIA performed similarly to resin composite that is in accordance with other studies 23,24 reporting that highviscosity GIC can be used as permanent restoration with satisfactory results over 2 years. Long-term resistance to abrasion of high-viscosity GIC can be achieved as long as early wear characteristics are improved and no premature loss of the protective resin layer occurred due to several factors such as aggressive brushing or bruxism.…”
Section: Discussionsupporting
confidence: 81%
“…birinci ve ikinci sınıf kavitelerde Equia ve rezin kompoziti karşılaştırdıkları randomize klinik çalışmanın, dört yıllık izlem sonucunda her iki restoratif materyali de benzer oranlarda başarılı bulmuşlardır. 44 Bu materyalin bir diğer avantajı ise renk seçeneği sunması ve bu sayede daha estetik sonuçların elde edilebilmesidir. 43 Giomer, önceden işleme sokulmuş cam iyonomer partikülü içeren restoratif bir materyaldir.…”
Section: Discussionunclassified
“…The recently introduced condensable GIC and a novel nano-filled resin coating material (Equia Restorative System; GC America, Alsip, IL) are reported to perform similarly to a microfilled hybrid composite in class 1 and 2 cavities at the end of 4 years [36]. However, no published data are available on the performance of these improved restorative materials in endodontically treated teeth; therefore, they should be used with caution.…”
Section: Glass Ionomer Cementmentioning
confidence: 97%